RELIGIOUS COMMUNICATION IN THE CONTEXT OF CULTURE MEDIA - Maria S. Petrushkevych (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of the work is to determine the features of media culture that bind it with mass culture and mass communications and have the most significant effect on the general principles of the religious mass communication. In addition, the objective is to identify the skills system and traits of mass human that are necessary for using media culture. Methodology. The methodological basis is related to structuring, analytical analysis and synthesis of media features; highlighting phenomena that illustrate modern communicative situation; characteristics of media trends influence for the specific functioning of religious communication. Scientific novelty. Main part of the work is devoted to the analysis of the progressive media culture, mass-media and their main features, design of religious communication in this culture. Media gradually form the appearance of religious communication quietly, especially the mass one, they adapt the modern religious discourse to rates of transfer and perception of information. Modern believer gets a lot of different kinds of religious information, on any subject, any explanation of the religious question, with respect to any religion. Such volume of religious information and the speed with which a person receives it, does not usually make it religious or spiritually advanced, but only informed. Spiritual perfection and religious development, religious communication is possible only when the customer is aware of media culture and way of seeing the ultimate goal of such communications using the Mass Media. So far these mechanisms are perfectly designed in traditional religious communication. Phenomena, that reflects the dramatic changes in the communicative environment are: mediatization of body and mind, the new practice of processing / reading information, the phenomenon of simultaneous perception of a large number of information channels – similar or different. Features of media culture that connect it with popular culture and are more likely to influence contemporary religious communication are such: visualization, technicality, handling large amounts of information, the creation of a specific picture of the world. Conclusions. Analyzed features of culture media give the possibility to draw conclusions about the necessary features that should have religious believer for successful communication with the help of modern media. These are: interactivity, constant access to information, the appropriate level of education (technical), conformity.